Zoe Marmer as Bee-Bee, Ashish Malhotra as Norman, Tim Roberts as Jeff, and Vasundhara Jolly as Pakeesa in 'subUrbia' (Tufts Archival Research Center, 2008)
Directed by Joe Pikowski. Production dates were 2010-03-04 to 2010-03-06.